Peran OJK dalam Pengawasan Hukum terhadap Praktik Perbankan di Indonesia - Muflikh, Alna Aulin Miftakhul; B, Baidhowi (Media Hukum Indonesia (MHI), 2025)
This study discusses the role of the Financial Services Authority (FIA) in the legal supervision of banking practices in Indonesia. Following the transfer of bank supervision functions from the Bank of Indonesia to the OJK through Law Number 21 of 2011, the OJK became an independent agency holding the primary authority in supervising the activities of the financial services sector, including banking. The study highlights the challenges that the OJK faces in carrying out its functions, such as the acceleration of digital finance innovation that exceeds regulatory readiness, the lack of inter-institutional coordination such as with the Bank of Indonesia and the Deposit Guarantor Institute (LPS), as well as human resource constraints in the areas of technology and digital law. Additionally, the effectiveness of OJK’s applied risk-based supervisory approach is also evaluated, particularly in terms of law violation prevention, consumer protection, and customer loss recovery. While progress has been made in regulatory formation such as the issuance of various OJK Regulations (POJK), the study concludes that OJK legal supervision of banking still requires structural reforms, strengthening of interagency coordination, and enhancement of financial institutional capacity and adaptive responsiveness to enable more complex industrial effects